Pengaruh Current Ratio, Debt To Equity Ratio, Dan Return On Equity Terhadap Dividend Payout Ratio Pada Perusahaan Indeks LQ45 - Dila Mawarsih; Dian Ayu Andriani (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to examine the effect of Current Ratio, Debt to Equity Ratio, and Return on Equity on Dividend Payout Ratio in LQ45 index companies listed on the Indonesia Stock Exchange. The study used secondary data obtained from published financial statements. The research sample consisted of 45 companies with a three-year observation period (2022–2024), resulting in 48 observations. The data were analyzed using multiple linear regression analysis. The results showed that partially the Current Ratio did not have a significant effect on Dividend Payout Ratio with a t-statistic value of -0,575 > t-table value of -2,01410 and a significance value of 0,568 > 0,05. The Debt to Equity Ratio did not have a significant effect on Dividend Payout Ratio with a t-statistic value of -1,938 > t-table value of -2,01410 and a significance value of 0,059 > 0,05. The Return on Equity showed a significant effect on Dividend Payout Ratio with a t-statistic value of 3,643 > t-table value of 2,01410 and a significance value of 0,001 < 0,05